Biodiesel production using simultaneous esterification-transesterification method from waste cooking oil with CaO/Fe2O3 bifunctional catalyst - Buchori, Luqman; Widayat, Widayat; Anggoro, Didi Dwi; Sulardjaka, Sulardjaka; Aqiila, Ammara; Putri, Nadia Rizki Pramesti Setya (Edelweiss Applied Science and Technology, 2025)
Biodiesel is one of the products resulting from the initiation of energy diversification which can overcome the energy crisis both in Indonesia and in the world. Biodiesel can reduce combustion emissions. The purpose of this study was to produce biodiesel from waste cooking oil (WCO). The study was conducted using the simultaneous esterification-transesterification method with the help of a catalyst. The catalyst used was a bifunctional catalyst, namely CaO/Fe2O3. Waste cooking oil raw materials and biodiesel products were analyzed by GC-MS, while the catalyst was analyzed by SEM-EDX and XRD. The catalyst calcination temperature was varied at 750-950°C and the esterification-transesterification reaction time was varied at 1-5 hours. The results of the study showed that the highest biodiesel yield was obtained at 82% at a catalyst calcination temperature of 800°C and a reaction time of 4 hours. The methyl ester composition formed was 97.61%. The research results show that the biodiesel products produced comply with SNI 7182-2015 standards. This finding proves that waste cooking oil can be used as a raw material for biodiesel so that it will reduce the impact of environmental pollution.